Didactic Design of the Concept of Surface Area of Flat-Sided Prism Based on van Hiele’s Theory in Online Learning - Aziiza, Yushilatu Felayati; Rosjanuardi, Rizky; Juandi, Dadang (Mathematics Education Journal, 2022)
This research aimed to develop a didactic design of the concept of the surface area of a flat-sided prism by considering the stages of van Hiele’s theory as a learning trajectory. The didactic design of the concept of the surface area of a flat-sided prism based on van Hiele’s theory has been adapted to the pandemic situation and implemented to online learning. The research method employed was a qualitative method with data collected through observation, interviews, and documentation. The initial step in this research was to test the concept of the surface area of a flat-sided prism on 53 9th-grade students for the 2019/2020 school year to identify learning obstacles. Following the identification of the learning obstacles, an initial didactic design was then drawn up by applying the phases in van Hiele’s model of geometric thinking. The didactic design prepared was subsequently implemented online to 8th-grade junior high school students. The results of the implementation of the didactic design were analyzed as the final product. The conclusion from this research is that by using a didactic design that considers the stages of van Hiele geometry in understanding the concept of surface area of a flat-sided prism, it can help students understand the concept of a flat-sided prism correctly. It was found that students' understanding of the concept of the surface area of a prism improved from visual level to informal deduction.DOI : https://doi.org/10.22342/jpm.16.1.13789.73-88